Quantifying Impacts of Mean Annual Lake Bottom Temperature on Talik Development and Permafrost Degradation Below Expanding Thermokarst Lakes on the Qinghai-Tibet Plateau - Ling, Feng; Pan, Feifei (Water, 2019)
Paper examines the impacts of variations in the mean annual lake bottom temperature (MALBT) on talik development and permafrost degradation beneath expanding thermokarst lakes in the Beiluhe Basin on the Qinghai–Tibetan Plateau.